PERAN INOVASI PEMBELAJARAN PENJAS DALAM MENINGKATKAN KESEHATAN FISIK SISWA TINJAUAN SISTEMATIK - Ilham Kamaruddin; Indra Adi Budiman; M. Torero Rigel Centeury; Jonika Trishandra; Hendri Mulyadi; Muhammad Rifai (EDU RESEARCH, 2024)
This study aims to examine the role of innovation in Physical Education (PE) learning in improving students' physical health through a systematic review. In an increasingly digital era, innovative approaches in PE learning are crucial to attract students' interest in physical activities that are directly related to their health. This research identifies different types of innovations applied in PE learning, including the use of technology, fitness apps, and gamification, and their impact on improving students' physical fitness. Based on literature analysis from various relevant sources, the results show that the use of technology and interactive methods in PE learning can increase students' engagement in sports, as well as encourage healthy lifestyle changes that have a positive impact on students' physical health. In addition, challenges faced in implementing this innovation, such as limited facilities and teacher training, are also reviewed to provide policy recommendations that can support the success of learning innovations. This research is expected to provide useful insights for curriculum development and learning strategies for PE that are more effective and in line with the times.